2011
DOI: 10.1176/appi.ajp.2011.10101446
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase Genotype Modulation of Impulsivity and Ventral Striatal Activity in Adult ADHD Patients and Healthy Comparison Subjects

Abstract: (5), as evidenced by steeper temporal discounting rates, altered decision making, and an aversion to delay of gratification in reward-related tests (6-9). Temporal discounting is the patient's preference to receive smaller rewards sooner rather than larger rewards later and is postulated to be an intermediate phenotype for impulsivity. Neuroimaging studies have shown engagement of alternative brain regions in decision making in ADHD patients (10). A prominent feature is hypoactivation of the ventral striatum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 37 publications
7
82
0
Order By: Relevance
“…In this sense, motivational deficiencies may be derived from a lack of stimulus-outcome contingency awareness (i.e., an impairment within the circuitry detailed in Figure 1C). The relatively consistent finding of hypo-activation in the ventral striatum during reward anticipation supports this idea (Scheres et al, 2007; Ströhle et al, 2008; Plichta et al, 2009; Hoogman et al, 2011; Carmona et al, 2012; Edel et al, 2013; Plichta and Scheres, 2013). Wilbertz et al (2012) found increased OFC activation during outcome delivery consistent with increased excitation to reward; however, as reward-related stimuli were generally less successful at inducing reward anticipation, it may also reflect an aberrant prediction error-like response.…”
Section: The Breakdown Of Goal-directed Processes In Psychiatric and mentioning
confidence: 66%
“…In this sense, motivational deficiencies may be derived from a lack of stimulus-outcome contingency awareness (i.e., an impairment within the circuitry detailed in Figure 1C). The relatively consistent finding of hypo-activation in the ventral striatum during reward anticipation supports this idea (Scheres et al, 2007; Ströhle et al, 2008; Plichta et al, 2009; Hoogman et al, 2011; Carmona et al, 2012; Edel et al, 2013; Plichta and Scheres, 2013). Wilbertz et al (2012) found increased OFC activation during outcome delivery consistent with increased excitation to reward; however, as reward-related stimuli were generally less successful at inducing reward anticipation, it may also reflect an aberrant prediction error-like response.…”
Section: The Breakdown Of Goal-directed Processes In Psychiatric and mentioning
confidence: 66%
“…The genetic and neuroimaging data are described elsewhere (i.e. (Franke et al, 2010; Hoogman et al, 2011)). For session 2, participants were requested to withhold stimulant medication 24 hours prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, youths and adults with ADHD (Hoogman, et al, 2011; Plichta & Scheres, 2014; Scheres, Milham, Knutson, & Castellanos, 2007), adolescent smokers (Peters, et al, 2011) and adolescent Met carriers (Nees, et al, 2015) also show reduced mesolimbic responses on the MID. On the other hand, greater mesolimbic MID response has been associated with higher approach motivation (Hahn, et al, 2009; Kennis, Rademaker, & Geuze, 2013; Simon, et al, 2010), trait positive affect (Wu, Samanez-Larkin, Katovich, & Knutson, 2014), higher sensation seeking (Abler, Walter, Erk, Kammerer, & Spitzer, 2006; Bjork, Knutson, & Hommer, 2008), and presence of or risk for externalizing disorders (Bjork, Chen, Smith, & Hommer, 2010; Bjork, Smith, Chen, & Hommer, 2011; Heitzeg, et al, 2014; Hoogman, et al, 2011; Yau, et al, 2012). In addition, high impulsivity shows a trend to be positively correlated with sensitivity to large versus small incentive values (Vaidya, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%